A study of children’s health in S.Paulo city (Brazil), 1984-1985: III -Breast feeding - Monteiro, Carlos Augusto; Pino Zuñiga, Hilda Paulina; Benício, Maria Helena D'Aquino; Rea, Marina Ferreira (Revista de Saúde Pública, 1987)
A survey of 1,016 children under five years old, randomly sampled was carried out in S.Paulo city, Brazil, with a view to studying the epidemiology of health conditions. In this survey the prevalence and duration of breast feedind were particularly observed. Although the majority of infants start breast feeding (92.8%), less than a half are still nursed at 4 months, 18.8% at 12 and 10.7% at 24 months. The median duration of breast feeding for S.Paulo city was estimated at 109.25 days. As far as exclusive breast feeding is concerned, the median duration decrease to 62.85 days. When the sample was stratified according to socioeconomic status, the breast feeding rates (total or exclusive, as medians) are higher on the highest socioeconomic level, an unusual situation in developing countries. The comparison of data of the 1984/85 survey with those of 1973/74 and 1981 shows an evident trend to return to the practice of breast feeding in S.Paulo. This trend is similar to that found in developed countries during the 70's, specially for the highest socioeconomic status, documented for other great urban conglomerates of the Third World. Although the trend can be considered incipient, because many infants are still weaned early, it shows there is no reason to accept as irreversible the trend towards artificial feeding in urban societies of the Third World.